MEDAN MAKNA VERBA JATUH BAHASA DAYAK PANDU - Parisna, Lisa; Sukamto, Sukamto; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research focuses on one field of semantic study of the field meaning verbs fall in BDP. The general problem in this study was